1999
DOI: 10.1007/pl00006811
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Transcription of Toxin DNA in a Nontoxigenic Strain of Clostridium difficile

Abstract: Genomic DNA from three Clostridium difficile strains was analyzed by PCR for DNA sequences encoding toxin A (tcdA) and toxin B (tcdB). Toxigenic control strain VPI 10463 possessed tcdA, tcdB, and an open reading frame (tcdE) between these two genes, whereas nontoxigenic control strain 85 lacked each of these genetic determinants. However, strain M90, also a nontoxigenic strain, was found to possess tcdA, tcdB, and tcdE. Normally the presence of toxin genes is associated with toxigenicity. Analysis of tcdA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Mathis et al (1999) reported the detection of a DNA sequence portion of both tcdA and tcdB by PCR and very low levels of mRNA of these genes in a specific non-toxigenic strain of C. difficile. Maybe this is the case of the strains belonging to PCR-ribotype 133 described by Alcides and co-workers (2007), where the levels of TcdA and TcdB were too low to be detected by ELISA assay.…”
Section: Discussionmentioning
confidence: 98%
“…Mathis et al (1999) reported the detection of a DNA sequence portion of both tcdA and tcdB by PCR and very low levels of mRNA of these genes in a specific non-toxigenic strain of C. difficile. Maybe this is the case of the strains belonging to PCR-ribotype 133 described by Alcides and co-workers (2007), where the levels of TcdA and TcdB were too low to be detected by ELISA assay.…”
Section: Discussionmentioning
confidence: 98%
“…The tcdB gene is a preferable target to tcdA because it allows the detection of increasingly prevalent toxin A-negative, toxin B-positive strains (4,13,15,26,27,30,36,41,48,49), as well as strains producing both toxins A and B. Strains that carry tcdB but exhibit low levels of expression (38) or produce toxin A only (17) appear to be very uncommon. Although Sloan et al have suggested tcdC to be a suitable target for PCR detection of toxigenic C. difficile (50), the variability of tcdC (53,55) and its dispensability for virulence raise concerns about its long-term stability as a diagnostic target.…”
Section: Discussionmentioning
confidence: 99%
“…Toxinotype XI strains could have only part of the PaLoc left or they could possess regions of the PaLoc that cannot be detected using the current PCR primers. A nontoxigenic C. difficile strain that should have both toxin genes was described by Mathis et al (1999).…”
Section: Discussionmentioning
confidence: 99%